A Rare Case of Suppurative Aspergillosis of the Thyroid - Nikhil Dinaker Thada; Sampath Chandra Prasad; Bhasker Alva; Monika Pokharel; Kishore Chandra Prasad (Case Reports in Otolaryngology)
Suppurative fungal infection of the thyroid is an extremely rare condition even more so in an immunocompetent patient. Fungal infections of the thyroid usually occur in immunocompromised patients with hematological malignancies, recipients of bone marrow and solid organ allografts on immunosuppression, and patients with AIDS. A 65-year-old male presented with swelling in the front of the neck for 2 years. Examination revealed a  cm non-tender, firm swelling of the right lobe of the thyroid. The patient was taken up for a subtotal thyroidectomy. Intra-operatively, an abscess cavity with pus was found in the right lobe of the thyroid. Histopathology revealed features of fungal abscess and staining demonstrated fungal hyphae characteristic of Aspergillus ssp.